PENGARUH MODEL DOUBLE LOOP PROBLEM SOLVING BERBANTUAN MEDIA PHOTO STORY TERHADAP KEMAMPUAN MENULIS TEKS BERITA SISWA KELAS VIII MTS AR-RASYID SEI RENGGAS T.A 2025/2026 - Indah Rahma Dhini; Mapilindo Mapilindo (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2026)
The study aims to determine the effect of the double loop problem-solving model assisted by photo story media on the news text writing skills at VIIIth Grade Students of MTS Ar-Rasyid Sei Renggas in 2025/2026 Academic Year. The problem in this study is the students' low ability in writing news texts, especially in understanding news structure, the 5W + 1H elements, and the use of appropriate linguistic rules. The type of research used is quantitative with an experimental method using a Posttest Only Control Group Design. The population in this study are all 56 eighth-grade students of MTS Ar-Rasyid Sei Renggas. The sampling technique used total sampling, so the entire population was used as the research sample. The research instrument was a news text writing ability test. The results showed that the news text writing ability in the experimental class was better than the control class, the average score of the control class was 66.42, categorized as sufficient, while the experimental class obtained an average score of 79.29, categorized as good. Based on the results of the hypothesis test using the t-test, it was obtained that t count > t table, namely 5.59 > 1.67, so the null hypothesis (Ho) that there is no significant effect is rejected and the alternative hypothesis (Ha) that there is a significant effect of the use of Photo story media on the news text writing ability at VIIIth-grade students of MTS Ar-Rasyid Sei Renggas in 2025/2026 Academic Year is accepted.